PENGARUH PELATIHAN DAN SUPERVISI KEPALA SEKOLAH TERHADAP KOMPETENSI GURU DI SEKOLAH NEGERI KECAMATAN JATI KABUPATEN KUDUS TAHUN 2020 - Redjeki Handayani; Sukirman Sukirman; Santoso Santoso (Universitas Muria Kudus, 2021)
The objectives of this study are: 1) Describe the planning of training and supervision of training school principals on teacher competence at the Elementary Schools in Jati Subdistrict, Kudus Regency in 2020. 2) Describe the implementation of training and supervision of school principals on teacher competence in SD Negeri Jati District, Kudus Regency Tahun 2020 3) Describe the follow-up of training and supervision of school principals on the competence of teachers in SD Negeri Jati District, Kudus Regency, 2020. This research is a quantitative research. The data collection methods used were questionnaires, observation and literature study. The population in this study amounted to 315 samples, 74, while the data analysis was multiple linear regression analysis and hypothesis testing. The results showed that: 1) The effect of training on the competence of elementary school teachers in Jati Subdistrict, Kudus Regency in 2020. The results of hypothesis 1 testing indicate that training has a significant effect on teacher competence where the t value is 2.134 and the probability (sig-t) is 0.002. 0.05, and t table n = 74 of 1.992, then the value of t count t table (2.134 1.993), 2) The effect of principal supervision on the competence of teachers in Public Elementary Schools, Jati District, Kudus Regency, 2020. Results of hypothesis testing 2 shows that the count is 2.462 and the probability (sig-t) is 0.002 0.05, and t table n = 74 is 1.993, then t count t table (2.462 1.993). 3) The effect of training and supervision of school principals on the competence of teachers in SD Negeri Jati Subdistrict, Kudus Regency in 2020. The results of testing for hypothesis 3 show that the value of F count = 6.293 and probability (Sig-F) of 0.003 0.05. This shows that the probability is less than the 5% significance level (p 0.05), and the F table is 3.13. Due to the value of F count F table (6.293 3.13). This study shows that the supervision of the principal is very important in increasing the competence of teachers in schools. Therefore the principal must increase the effectiveness of his supervision so that teacher performance can increase.